New Trend of Promotional Strategies in Bangladesh: A Study on the Acceptance and Influence of Product Placement from Consumers Standpoint. (Global Journal of Management and Business Research, 2017)
The study intends to contribute to a more serious understanding of consumer acceptance of product placement and its influence on purchase intention of consumers. 168 respondents from different cities of Bangladesh participated in the study. The methodology of the study designed using the true experimental method. Collected data has been analyzed via SPSS windows software version 24. This study is guided by the Theory of Reasoned Action, which recommends that individual consumers' behavior is guided by their purchase intention. the consumer awareness of product placement does not influence the consumer attitude toward product placement significantly. It may have its impact on consumer behavior but it’s not a major influence. The study also suggests that consumer attitude toward product placement is the most influential variable than the consumer attitude in shaping consumer purchase decision and product placement may not have a huge impact on consumer purchase decision.
Keywords: product placement; consumer behavior; purchase intention; acceptance; attitude